Communication and New Literacies in the multicultural world - Varis, Tapio (Historia y Comunicación Social, 2010)
Knowledge and skills for international and intercultural interaction are needed in nearly all fields. This is why multicultural studies should be made an integral part not only of general education but also of adult and vocational education and training. In an intercultural world communication necessarily mediates different values and cultural behaviours. Great civilizations and cultures have very different patterns of communication and use different senses in a different way. In consequence, if a truly global information society is to be created, more attention should be given to the diversity of cultures and the co-existence of different civilizations and cultures.. Digital literacy as media literacy aims to develop both critical understanding of and active participation in the media. Using a computer requires diverse and complex previous knowledge. It also introduces the individual and humanity to new contexts, which demands mental, intellectual, profound and complex changes. Creativity and culture become essential raw materials for the knowledge economy.